MODEL PENERAPAN CORPORATE SOCIAL RESPONSIBILITY OLEH MULTINATIONAL CORPORATION DALAM PENGATURAN INTERNATIONAL FINANCE CORPORATION (IFC) DAN MULTILATERAL INVESTMENT GUARANTEE AGENCY (MIGA) - Hikmatul Ula (Arena Hukum, 2014)
AbstractThe research focuses on the legal position of Corporate Social Responsibility by Multinational Corporation in the regulation of the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA) and the implementation model of Corporate Social Responsibility by Multinational Corporation in the regulation of the International Finance Corporation (IFC) and the Multilateral Investment Guarantee Agency (MIGA). By using the method of normative research with conceptual and analytical approach, it can be seen that the legal status of CSR in the setting of international law is voluntary norm. But in its development, IFC and MIGA position not only as the voluntary CSR norm but important condition that must be met by each company that will work with IFC and MIGA (obligatory norm). The model of Implementation of CSR in IFC and MIGA can be described in two stages, before the execution of corporate business activities (prevetive action) and after running the corporate business activities (repressive and evaluative action). As a preventive action IFC and MIGA requires every corporation to meet established performance standards particularly in terms of environmental and social. As repressive and evaluative methods, the WBG has a duty CAO institution and its function is to receive complaints and grievances of the people associated with the firm in cooperation with the IFC or MIGA. Key words: implementasi, CSR, WBG, IFC, MIGA, voluntary, obligatory norm Â AbstrakÂ Penelitian itu menitikberatkan pada kedudukan hukum Corporate Sosial Responsibility oleh Multinasional Corporation dalam pengaturan International Finance Corporation (IFC) dan Multilateral Investment Guarantee Agency (MIGA) dan model penerapan Corporate Social Responsibility oleh Multinasional Corporation dalam pengaturan International Finance Corporation (IFC) dan Multilateral Investment Guarantee Agency (MIGA). Dengan menggunakan metode penelitian yuridis normatif dengan pendekatan konseptual dan analisis, dapat diketahui bahwa Kedudukan hukum CSR dalam pengaturan hukum internasional adalah voluntary norm. Namun dalam perkembangannya IFC dan MIGA memposisikan CSR bukan hanya sebagai voluntary norm tetapi syarat penting yang harus dipenuhi oleh setiap perusahaan yang akan bekerja sama dengan IFC dan MIGA (obligatory norm). Model pelaksanaan CSR dalam IFC dan MIGA dapat dijelaskan dalam dua tahap yaitu sebelum dilaksanakannya kegiatan usaha korporasi (prevetif action) dan setelah kegiatan usaha korporasi berjalan (represif dan evaluatif action). Sebagai preventif action IFC dan MIGA mensyaratkan setiap korporasi untuk memenuhi standar kinerja yang telah ditetapkan khususnya dalam hal lingkungan dan sosial. Sebagai metode represif dan evaluatif, WBG memiliki lembaga CAO yang tugas dan fungsinya adalah menerima pengaduan dan keluhan dari masyarakat terkait dengan perusahaan yang bekerjasama dengan IFC atau MIGA.Kata kunci: implementasi, CSR, WBG, IFC, MIGA, voluntary, obligatory norm